ALAT PENDIDIKAN ISLAM VIA ARTIFICAL INTELLIGENT (AI)PERSPEKTIF TECHNOLOGICAL, PEDAGOGICAL, AND CONTENT KNOWLEDGE (TPACK) - Kartika Sari Dwi Nuraini; Muthia Zahrotul Jannah; Moh Faizin (CV. Adiba Aisha Amira, 2025)
The development of digital technology has had a significant impact on the education sector, including in the realm of Islamic education. One innovation that plays a crucial role is artificial intelligence (AI). This article explains how AI can be used as a tool in Islamic education using the TPACK approach, which encompasses knowledge of technology, pedagogy, and content. This research was conducted through a literature review analyzing various existing literature. The findings of this study indicate that AI can increase the effectiveness of the Islamic learning process and maintain the teacher's position as a moral and spiritual guide.